Agrotechnics Of Plantation From Seeds Of Silic Sweets (Glycyrrhiza Glabra L) - Nuranovna, Abdalova Guliston; Nezamiddinovna, Urmanova Munisa; Koylibaevna, Ajiniyazova Mexriban; Kholikulovich, Aliev Jurakul; Vali o’gli, Toshpulatov Chingizkhan (International Journal of Psychosocial Rehabilitation, 2020)
The article presents an analysis of the results of research on agronomic techniques of seedling cultivation from the seeds of smooth licorice (glycyrrhiza glabra L). The analysis of research results on the effect of irrigation regimes on the growth and development of smooth licorice seedlings, the analysis of experimental work on the effects of smooth licorice irrigation regimens and mineral fertilizer rates on winter wheat yields was carried out. The cost-effectiveness of growing seedlings from smooth licorice seeds was also studied by analyzing the results of irrigation procedures, the effect of licorice on soil fertility, as well as the growth, development and yield of winter wheat planted as a follow-up crop after two years of seedlings. Based on the results of the experiment, conclusions and recommendations were developed.